Short report: Inhibition by tumor necrosis factor-alpha-activated macrophages of the transition of Paracoccidioides brasiliensis conidia to yeast cells through a mechanism independent of nitric oxide (2004)
ABSTRACT : It is known that peritoneal murine macrophages activated with interferon- exert a fungicidal effect againstParacoccidioides brasiliensisconidia by a nitric oxide (NO)−mediated mechanism. This NO-mediated effect can also beinduced by other cytokines such as tumor necrosis factor- (TNF- ). The aim of this study was to determine ifTNF- −activated peritoneal murine macrophages infected withP. brasiliensiswere able to show fungistatic/fungicidaleffects mediated by NO. The results indicated that although macrophage activation with TNF- did not result in NOproduction, these cells played an important role in inhibiting the conidia from becoming yeast cells.In vivo, theNO-independent inhibitory effect would prove of importance for the establishment ofP. brasiliensisin host tissues.